2020
DOI: 10.1016/j.snb.2019.127194
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous silica films for sensing volatile organic compounds using attenuated total reflection spectroscopy

Abstract: Sensitivity of evanescent wave sensing of gaseous species can be vastly increased by enrichment materials that locally concentrate the analyte on the sensor. Here, we investigate functionalized mesoporous silica films as versatile enrichment layer for sensing volatile organic compounds (VOCs) from gas-phase. Attenuated total reflection (ATR) crystals were coated with silica films of different pore sizes and their capability to enrich three different aromatic hydrocarbons from a vapor stream was studied by mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Hydrophobicity was attained by simultaneous template removal and functionalization in acetone. A similar approach was used for the determination of toluene, p-xylene and trimethylbenzene from water vapor two years later by the same group (Baumgartner et al, 2020b) (Figures 5C,D). In this case, samples were calcinated to 400°C and a postgrafting step was done in toluene.…”
Section: Claddings On Atr Crystalsmentioning
confidence: 98%
See 1 more Smart Citation
“…Hydrophobicity was attained by simultaneous template removal and functionalization in acetone. A similar approach was used for the determination of toluene, p-xylene and trimethylbenzene from water vapor two years later by the same group (Baumgartner et al, 2020b) (Figures 5C,D). In this case, samples were calcinated to 400°C and a postgrafting step was done in toluene.…”
Section: Claddings On Atr Crystalsmentioning
confidence: 98%
“…Haolan Zhao et al reported a VOC sensing chip based on silicon nitride waveguides for Raman spectroscopy (Zhao et al, 2020). Here, they followed the same coating protocol applied on ATR crystals for determination of benzonitrile and valeronitrile from a water matrix as in (Baumgartner et al, 2018) (Baumgartner et al, 2020b). An even more recent report described an hydrophobic mesoporous silica coating spin-coated on germanium waveguide structures for measuring toluene in water following the same idea proposed by Lopez and Brinker in 1996 on ATR crystals ( Figure 6B) (Benéitez et al, 2020).…”
Section: Claddings On Integrated Waveguidesmentioning
confidence: 99%
“…In contrast to using polymer coatings, surface modification in mesoporous films also allows to adjust the selectivity as required. This concept has been recently demonstrated on ATR crystals using functionalized mesoporous silica coatings for detecting benzonitrile and valeronitrile as examples for apolar molecules, as well as nitrate as an example for a polar analyte in water [23,24]. Furthermore, again employing miniaturized multi-bounce ATR crystals, expansion of this concept to gas sensing of aromatic hydrocarbons has been shown too [24].…”
Section: Chip-based Evanescent Wave Sensing Platformmentioning
confidence: 99%
“…However, IMS has a limited specificity, and it often encounters challenges in quantifying separate VOC components in complex samples [5,6]. Mid-infrared absorption spectroscopy has been implemented to VOC sensing [7,8]. Integrated midinfrared sources and detectors, however, are not widely available yet, hurdling the miniaturization of this method.…”
mentioning
confidence: 99%
“…The densities of pure IPA liquid and 103 ppm IPA vapor are 13 and 4.6 µmol/L, respectively; considering the difference in mode overlap on uncoated and coated waveguides, the partition coefficient of the coating is estimated to be 2.3 × 10 4 . Modifications of the coating can further improve the partition coefficient [8], enabling sub-10 ppm sensing with 1 s integration time.…”
mentioning
confidence: 99%